2023
DOI: 10.1055/s-0043-1768062
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Stress in Recurrent Aphthous Stomatitis

Abstract: Objectives This study aimed to determine the role of stress in recurrent aphthous stomatitis. Stress was examined with the Perceived Stress Scale and cortisol levels; meanwhile, recurrent aphthous stomatitis was assessed with the duration of the lesion. Materials and Methods This was a cross-sectional analytical study conducted at Oral Medicine Installation, Universitas Sumatera Utara Dental Hospital, and Prodia Laboratory, Medan. The subjects were 50 patients with minor recurrent aphthous stomatitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…According to some studies, the majority of people with RAS had the ailment before the age of 30, with the condition peaking in their 20s. As one ages, the frequency of active lesions has shown a decline [4]. Females had a higher prevalence of the lesion in our sample than males.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…According to some studies, the majority of people with RAS had the ailment before the age of 30, with the condition peaking in their 20s. As one ages, the frequency of active lesions has shown a decline [4]. Females had a higher prevalence of the lesion in our sample than males.…”
Section: Discussionmentioning
confidence: 51%
“…Previous studies also found that females were more likely than males to suffer from RAS, in both children and adults. Some studies attribute this greater prevalence of RAS in females to hormonal differences between the two sexes [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results in this study align with the study conducted by Nurdiana et al, that showed 75.8% of subjects had moderate stress levels as predisposing factor for RAS. [30][31][32] Stress can create habits that can damage the oral mucosa, such as biting the lips and cheeks, which eventually causes RAS. 31 when a person experiences stress, the body will produce more cortisol.…”
Section: Discussionmentioning
confidence: 99%